2010
DOI: 10.1111/j.1600-0501.2009.01891.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histomorphometric evaluation of extraction sockets treated with an autologous bone marrow graft

Abstract: These findings suggest that the autologous bone marrow graft can contribute to alveolar bone repair after tooth extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(175 citation statements)
references
References 27 publications
(59 reference statements)
5
167
1
2
Order By: Relevance
“…A wide range of biomaterials, including autografts [9], allografts [10], xenografts [11], alloplastic materials such as bioactive glasses [12], autogenous tooth bone grafts [13][14][15], bioactive materials such as recombinant human bone morphogenetic protein-2 (rhBMP-2) [16], and platelet-rich fibrin (PRF) [17], has been shown to produce positive outcomes for ridge preservation. Autogenous bone is an ideal material for hard tissue defects because it has osteoinduction and osteoconduction and has no immune rejection.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of biomaterials, including autografts [9], allografts [10], xenografts [11], alloplastic materials such as bioactive glasses [12], autogenous tooth bone grafts [13][14][15], bioactive materials such as recombinant human bone morphogenetic protein-2 (rhBMP-2) [16], and platelet-rich fibrin (PRF) [17], has been shown to produce positive outcomes for ridge preservation. Autogenous bone is an ideal material for hard tissue defects because it has osteoinduction and osteoconduction and has no immune rejection.…”
Section: Introductionmentioning
confidence: 99%
“…It is because when Aloe vera is combined with XCB which is osteoinduction, it will accelerate healing process and new bone growth. 2,8,9,10 The increasing of osteoblast will not occur continuously, but at a certain time it will decrease. In a previous study, it is known that the growth of osteoblasts in tooth extraction socket filled with Aloe vera and XCB with 0.5% concentration of the active substance increased on day 30, but on histologic examination it is known that the growth of osteoblasts decreased on day 60.…”
Section: Osteoblastmentioning
confidence: 99%
“…The decreasing even occurs several times due to residual ridge resorption that physiologically occurs after tooth extraction. 2 Residual ridge resorption is a biomechanical disease caused by multi-factors, such as anatomic, metabolic, and mechanical determinants. 3 After tooth extraction, there will usually be inflammation as rapid reaction in the area of extraction, and the sockets of the extraction will be filled with blood clot.…”
mentioning
confidence: 99%
“…In the literature numerous clinical studies have reported dimensional width change varying from 23-66% (2.1 mm to 4.9 mm) after extraction alone (Lekovic et al 1997, Lekovic et al 1998, Camargo et al 2000, Iasella et al 2003. Barone et al 2008, Pelegrine et al 2010, Festa et al 201 L Brownfield & Weltman 2012, Cardaropoli et al 2012. Ridge alterations can significantly affect the placement of dental implants in the desired position with severe consequences in occlusion and esthetics.…”
Section: Alveolar Ridge Resorption Following Tooth Extractionmentioning
confidence: 99%